KOMPOSISI HASIL TANGKAPAN JARING INSANG PADA MUSIM KEMARAU DAN PENGHUJAN DI WADUK SERMO KABUPATEN KULON PROGO - , RISKA NILAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aims to evaluate the composition of catches of fish, the difference on a rainy and dry season, as well as a difference catches the eye of various sizes on the net. Research carried out July until November 2012 representing dry season and 2012 to March in December 2013 representing rainy season. The sampling done every two weeks by a gill net. The data composition used all the catch fish samples, meanwhile length, weight and sex data used 20 fishes each mesh size used. Analysis of data conducted to determine influence treatment of total of fish and weight catch fish (g) using Anova and Duncanâ s test, fish composition, length and weight fish distribution, and size fish caught analyzed in descriptive, while the ratio sex analyzed use Chi square (XÂ²) test. The result showed there is a real difference between the average total number and weight (gram) of fish against mesh size 1 inch